Versatile action of picomolar gradients of progesterone on different sperm subpopulations - Uñates, Diego Rafael (2014)
High step concentrations of progesterone may stimulate various sperm physiological processes, such as priming and the acrosome reaction. However, approaching the egg, spermatozoa face increasing concentrations of the hormone, as it is secreted by the cumulus cells and then passively diffuses along the cumulus matrix and beyond. In this context, several questions arise: are spermatozoa sensitive to the steroid gradients as they undergo priming and the acrosome reaction? If so, what are the functional gradual concentrations of progesterone? Do spermatozoa in different physiological states respond differentially to steroid gradients? To answer these questions, spermatozoa were confronted with progesterone gradients generated by different hormone concentrations (1 pM to 100 μM). Brief exposure to a 10 pM progesterone gradient stimulated priming for the acrosome reaction in one sperm subpopulation, and simultaneously induced the acrosome reaction in a different sperm subpopulation. This effect was not observed in non-capacitated cells or when progesterone was homogeneously distributed. The results suggest a versatile role of the gradual distribution of very low doses of progesterone, which selectively stimulate the priming and the acrosome reaction in different sperm subpopulations. © 2014 Uñates et al.